Облава на волка: [роман] / Михаил Серегин - Серегин Михаил Георгиевич (Русский вор, 2002)
Экземпляры: Ф. 13 (20210521) / Инвентарный номер: 38384 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 32 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44